Laparoscopic Cholecystectomy is Associated with Superior Clinical Outcomes in Pediatric Cholelithiasis: A 6-Year Comprehensive Surgical Outcome Analysis from Semarang, Indonesia - Natasha Hartanto; Edwin Basyar; Rudiyuwono Raharjo (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: The incidence of pediatric cholelithiasis is increasing globally, driven primarily by the childhood obesity epidemic. In a nation of over 270 million people like Indonesia, with rising obesity rates, understanding the optimal surgical management is a national health priority. This study provides the first detailed, comparative surgical outcome analysis for pediatric cholecystectomy from a major Indonesian referral center. Methods: A retrospective cohort study of all pediatric patients (≤18 years) undergoing cholecystectomy from January 2019 to December 2024 was conducted. Data on preoperative demographics, clinical presentation, intraoperative variables (operative time, blood loss, conversion rate), and postoperative outcomes (length of stay, 30-day complications graded by Clavien-Dindo) were extracted. Laparoscopic (LC) and open cholecystectomy (OC) groups were compared using Mann-Whitney U and Fisher’s exact tests. Results: The cohort of 30 patients (70% female, mean age 12.0 years) had a 60% prevalence of overweight or obesity. Laparoscopy was the initial approach in 25 cases (83.3%), with one conversion to open surgery (4%). Compared to the OC group (n=6), the definitive LC group (n=24) demonstrated significantly superior outcomes: median operative time was shorter (72 vs. 115 minutes, p=0.004), median estimated blood loss was lower (15 vs. 80 mL, p<0.001), and median postoperative length of stay was significantly reduced (3 vs. 5 days, p=0.002). The postoperative complication rate was lower in the LC group (8.3% vs. 33.3%, p=0.14), with all complications being minor (Clavien-Dindo Grade I-II). Conclusion: Laparoscopic cholecystectomy is a safe, effective, and efficient procedure that provides superior clinical outcomes compared to the open approach in the Indonesian pediatric population. These findings provide robust local evidence to establish LC as the unequivocal standard of care and justify investment in minimally invasive surgical training and infrastructure to meet the rising burden of this disease.